Grapevine and Arabidopsis Cation-Chloride Cotransporters Localize to the Golgi and Trans-Golgi Network and Indirectly Influence Long-Distance Ion Transport and Plant Salt Tolerance . Issue 3 (16th September 2015) - Henderson, Sam W.; Wege, Stefanie; Qiu, Jiaen; Blackmore, Deidre H.; Walker, Amanda R.; Tyerman, Stephen D.; Walker, Rob R.; Gilliham, Matthew
Abstract : A protein from grapevine that transports sodium, potassium, and chloride ions across endomembranes is important for normal growth and salt tolerance. Abstract: Plant cation-chloride cotransporters (CCCs) have been implicated in conferring salt tolerance. They are predicted to improve shoot salt exclusion by directly catalyzing the retrieval of sodium (Na + ) and chloride (Cl − ) ions from the root xylem. We investigated whether grapevine ( Vitis vinifera [ Vvi ]) CCC has a role in salt tolerance by cloning and functionally characterizing the gene from the cultivar Cabernet Sauvignon. Amino acid sequence analysis revealed that VviCCC shares a high degree of similarity with other plant CCCs. A VviCCC-yellow fluorescent protein translational fusion protein localized to the Golgi and the trans-Golgi network and not the plasma membrane when expressed transiently in tobacco ( Nicotiana benthamiana ) leaves and Arabidopsis ( Arabidopsis thaliana ) mesophyll protoplasts. AtCCC-green fluorescent protein from Arabidopsis also localized to the Golgi and the trans-Golgi network. In Xenopus laevis oocytes, VviCCC targeted to the plasma membrane, where it catalyzed bumetanide-sensitive 36 Cl –, 22 Na +, and 86 Rb + uptake, suggesting that VviCCC (like AtCCC) belongs to the Na + -K + -2Cl – cotransporter class of CCCs. Expression of VviCCC in an Arabidopsis ccc knockout mutant abolished the mutant's stunted growth phenotypes and reduced shoot Cl – and Na + content to wild-type levels after growing plants in 50 mm NaCl. In grapevine roots, VviCCC transcript abundance was not regulated by Cl – treatment and was present at similar levels in both the root stele and cortex of three Vitis spp. genotypes that exhibit differential shoot salt exclusion. Our findings indicate that CCC function is conserved between grapevine and Arabidopsis, but neither protein is likely to directly mediate ion transfer with the xylem or have a direct role in salt tolerance.